Effectiveness of treatment of high-grade multiple cutaneous mast cell tumour using tyrosine kinase inhibitor and vinblastine: case report - Mujica, Paola C.; Bustamante, Marcia; Bascuñan, Lii; Sanhueza, Vicente (Universidad Nacional Mayor de San Marcos, 2021)
Cutaneous mast cell tumour is the most common skin neoplasm in dogs. The caseof a 10-year-old female Shar Pei canine patient is presented, who presented in consultationwith multiple erythematous masses on the medial aspect of the right hind limb. Bycytological and histopathological examination, high-grade mast cell tumour was diagnosed.The patient was treated with omeprazole and with a chemotherapy protocol based on acombination of vinblastine, prednisone, and a tyrosine kinase inhibitor. During the monthlyfollow-up of the evolution of the patient, partial remission of the masses was observed,which remained stable for seven months, at which time it was decided to suspend the useof vinblastine. After a month of this change, there was no recurrence of the previouslytreated masses; however, the appearance of new erythematous and ulcerated neoplasmsin another region of the affected hind limb was evidenced. This observation supports thehypothesis that the genetic nature of neoplasms of the same type, in the same patient,could be different and, therefore, determine the response to treatment and prognosis.
Efectividad del tratamiento de mastocitoma cutáneo múltiple de alto grado usando un inhibidor de tirosina quinasa y vinblastina: Reporte de caso
Keywords: High grade mast cell tumour; Cutaneous tumour; Tyrosine kinase inhibitor; Vinblastine; Prednisone